Utilization of Sugarcane Bagasse Ash to Improve Properties of Fired Clay Brick - Nonthaphong Phonphuak (Science Faculty of Chiang Mai University, 2019)
In this paper, the effects of incorporation of sugarcane bagasse ash (SCBA) on the properties of fired clay bricks were investigated. Clay bricks fabricated with 0, 2.5, 5, 7.5 and 10% by weight SCBA were tested. The clay brick specimens were fired at 900, 1000 and 1100 °C to study for water absorption, density, porosity and compressive strength of the brick samples were investigated. The bulk density of the tested specimens varied upon the SCBA dosage level and the dosage level of up to 10 wt.% was found to be satisfactory in this work. This was accompanied by the increases in water absorption and porosity and reduction in compressive strength of samples. The compressive strengths of bricks with 2.5 % SCBA fired at 1000 oC and with 2.5, 5.0 and 7.5 % SCBA fired at 1100 oC were higher than the required strength values as per ASTM C62-13a with beneficial reduced density and increased porosity. The firing shrinkage values were slightly increased with increasing in the SCBA content but were still within limit of the standard requirement. The results thus showed that SCBA was a potential material for use as a pore former additive to raw clay-brick production.